1985
DOI: 10.3758/bf03202499
|View full text |Cite
|
Sign up to set email alerts
|

Toward a translational model of Stroop interference

Abstract: Models ofthe Stroop effect that postulate single, centralized processing stations are fundamentally incorrect. A translational model is proposed in which parallel processing systems are hypothesized that are linked by a translation mechanism. Each system processes information using its own internal code specifically linked to the type of information the system processes. Information is passed between these systems via the translation mechanism. Evidence supporting this model comes from both the literature and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
291
6
4

Year Published

1988
1988
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(320 citation statements)
references
References 29 publications
19
291
6
4
Order By: Relevance
“…We have confirmed the Virzi and Egeth (1985) result using the present paradigm. Specifically, a version of our experiment was conducted in which the response labels were color patches rather than words.…”
Section: Notessupporting
confidence: 81%
See 2 more Smart Citations
“…We have confirmed the Virzi and Egeth (1985) result using the present paradigm. Specifically, a version of our experiment was conducted in which the response labels were color patches rather than words.…”
Section: Notessupporting
confidence: 81%
“…As Coltheart noted in his review of a previous version of this article, a translation between orthography and phonology occurs in reading aloud. Thus, the assertion by Virzi and Egeth (1985) and Sugg and McDonald (1994) that reading aloud does not require a translation makes their accounts difficult to understand.…”
Section: Notesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, perceptual similarity between the stimulus and response modes is primarily a factor when conceptual similarity is present (see also Lu & Proctor, 2001). The absence of the indicator of set-level differences due to perceptual similarity (i.e., the code-modality interaction for the congruent mapping) when S-R orientations are orthogonal and the S-R sets have structural but not conceptual similarity implies that there is not a fundamental distinction between spatial and linguistic systems, as is often hypothesized (e.g., Virzi & Egeth, 1985). Rather, the differences that are evident when the orientations are parallel and the S-R sets have conceptual similarity seem to be a function of subjects having more pre-experimental experiences with the same mode pairings of stimuli and their associated responses than with the different mode pairings (e.g., Alluisi et al, 1957).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown that Stroop interference can be significantly reduced by using non-naming responses such as buttonpressing (Flowers & Dutch, 1976;Keele, 1972;Virzi & Egeth, 1985). A possible explanation is that a printed word is "a program for a reader telling him how to pronounce it, but an object is not related to its name except arbitrarily" (Beller, 1975, p. 155).…”
mentioning
confidence: 99%